Seeds move! - Page, Robin, 1957- (Beach Lane Books, 2019)
Every seed, big or small, needs sunlight, water, and an uncrowded place to put down roots. But how do seeds get to the perfect place to grow? This exploration of seed dispersal covers a wide range of seeds and the creatures that help them move, from a coconut seed floating on waves to an African grass seed rolled by a dung beetle, to a milkweed seed floating on the wind.